Optimization Of Hybrid Carbon And Glass Fiber Reinforced Polymer Using Analytical Hierarchy Process - Md Zahir, Nur Aizatul 'Ain (2019)
Hybrid composite materials are known to be used in high precision industries. In order for mechanically hybrid composite laminates to be exploited for potential enabling technology, the laminates design of hybrid composite laminates should be practical and flexible enough to adapt to different design requirement such as stiffness, weight, thickness and cost. The existing of hybrid composite begins with the issues regarding cost, weight and mechanical properties when the researchers challenging themselves to develop the advanced mechanical properties of composite material with restricted manufacturing cost and lighter. Ten design configurations of unidirectional Carbon Fiber Reinforced Polymer (CFRP) combined with unidisoetional Glass Fiber Reinforced Polymer (GFRP) were developed and tested in the three-point-bending test in accordance with ASTM D790. GFRP has been known for low modulus high elongation material while CFRP on the other hand is high modulus low etlongation material. Thus by hybridization of a CFRP composite through the incorporation of GFRP would lead to lower material cost and density, a the same time improved the flexural properties of hybrid composite structure. The flexural properties of specimens were reconded and the failure modes is observed under scanning electron microscopic. The flexure test then was simulated by finite element analysis software, ANSYS APDL. Hence, a comparative.approach is helpful in the evaluation of design configuration of hybrid composite laminates in terms of flexural properties, weight and cost. In this study, a methodology for a combined five evaluated optimization criteria such as flexural strength, Strain to failure, flexural modulus, density and cost for CERP/GFRP. hybrid composite Jaminates is presented, The Analytical Hierarchy Process (AHP) is used as a dynamic tool for decision making in optimization of hybrid composite material that combining with experience, judgement and intuition with a view o selecting the best design configuration from ten design configurations alternatives. Ten design configurations were ranked by priority by using AHP and the results determined that the stacking sequence of composite laminates with CFRP plies placed at the outer layer of hybrid composite laminates could promote to the higher flexural strength thus can withstand higher stress experienced within the composite laminates before reach its failure load. These important findings could be used as a guide for design engineer in selecting and designing the most optimum design configurations for hybrid composite structure. The combination of a fundamental knowledge of the behaviour of composite laminates subjected to flexural loading and advanced modelling tool that can predict flexural properties, become a greatest help in optimization processes of hybrid composite laminates by extending the range of applications and performances of composite material.